Liquid crystal polymers: macromolecular design for enhanced performances - Paris, Fabio <1982> (Alma Mater Studiorum - Università di Bologna, 2010)
During this work, done mainly in the laboratories of the department of Industrial Chemistry and Materials of the University of Bologna but also in the laboratories of the Carnegie Mellon University in collaboration with prof. K. Matyjaszewski and at the university of Zaragoza in collaboration with prof. J. Barberá, was focused mainly on the synthesis and characterization of new functional polymeric materials. In the past years our group gained a deep knowledge about the photomodulation of azobenzene containing polymers. The aim of this thesis is to push forward the performances of these materials by the synthesis of well defined materials, in which, by a precise control over the macromolecular structures, better or even new functionality can be delivered to the synthesized material. For this purpose, besides the rich photochemistry of azoaromatic polymers that brings to the application, the control offered from the recent techniques of controlled radical polymerization, ATRP over all, gives an enormous range of opportunity for the developing of a new generation of functional materials whose properties are determinate not only by the chemical nature of the functional center (e.g. azoaromatic chromophore) but are tuned and even amplified by a synergy with the whole macromolecular structure. Old materials in new structures. In this contest the work of this thesis was focused mainly on the synthesis and characterization of well defined azoaromatic polymers in order to establish, for the first time, precise structure-properties correlation. In fact a series of well defined different azopolymers, chiral and achiral, with different molecular weight and highly monodisperse were synthesized and their properties were studied, in terms of photoexpansion and photomodulation of chirality. We were then able to study the influence of the macromolecular structure in terms of molecular weight and ramification on the studied properties. The huge amount of possibility offered by the tailoring of the macromolecular structure were exploited for the synthesis of new cholesteric photochromic polymers that can be used as a smart label for the certification of the thermal history of any thermosensitive product. Finally the ATRP synthesis allowed us to synthesize a total new class of material, named molecular brushes: a flat surface covered with an ultra thin layer of polymeric chain covalently bond onto the surface from one end. This new class of materials is of extreme interest as they offer the possibility to tune and manage the interaction of the surface with the environment. In this contest we synthesized both azoaromatic surfaces, growing directly the polymer from the surface, and mixed brushes: surfaces covered with incompatible macromolecules. Both type of surfaces acts as “smart” surfaces: the first it is able to move the orientation of a LC cell by simply photomodulation and, thanks to the robustness of the covalent bond, can be used as a command surface overcoming all the limitation due to the dewetting of the active layer. The second type of surface, functionalized by a grafting-to method, can self assemble the topmost layer responding to changed environmental conditions, exposing different functionality according to different environment.